Millisecond Conversion of Photovoltaic Silicon Waste to Binder‐Free High Silicon Content Nanowires Electrodes. Issue 40 (1st September 2021) - Lu, Jijun; Liu, Siliang; Liu, Junhao; Qian, Guoyu; Wang, Dong; Gong, Xuzhong; Deng, Yida; Chen, Yanan; Wang, Zhi
Abstract: High‐value recycling of photovoltaic silicon waste is an important path to achieve "carbon neutrality." However, the current remelting and refining technology of Si waste (WSi) is tedious with high secondary energy consumption and repollution, and it can only achieve its relegation recycling. Here, an efficient and high‐value recycling strategy is proposed in which photovoltaic WSi is converted to high energy density and stable Si nanowires (SiNWs) electrodes for lithium‐ion batteries (LIBs) in milliseconds. The flash heating and quenching (≈2100 K, 10 ms) provided by an electrothermal shock drive directional diffusion of Si atoms to form SiNWs within the confined space between graphene oxide films. As a result, the SiNWs self‐assemble to form a conductive SiNWs–reduced graphene oxide composite (SiNWs@RGO). When applied as a binder‐free anode for LIBs the SiNWs@RGO electrode exhibits an ultrahigh initial Coulombic efficiency (89.5%) and robust cycle stability (2381.7 mAh g −1 at 1 A g −1 for more than 500 cycles) at high Si content of 76%. Moreover, full LIBs constructed using the commercial Li[Ni0.8 Co0.16 Al0.04 ]O2 cathode exhibit impressive cycling performance. In addition, this clean high‐value recycling method will promote economic, environmentally friendly, and sustainable development of renewable energy. Abstract : An electrothermal shock method that directly converts photovoltaic silicon waste to Si nanowires (SiNWs) electrodes in milliseconds is proposed. The SiNWs electrode has a Si content of 76%, and exhibits ultrahigh initial Coulombic efficiency (89.5%) and stable half/full cell cycle performance. Successful application of this method opens a new pathway for promotion of the sustainable development of renewable energy.